PETROGRAFI BATUAN BEKU VOLKANIK BAWAH LAUT KOMPLEKS GUNUNG KOMBA, LAUT FLORES, INDONESIA - -, Johanes Hutabarat; -, Agus Didit Haryanto; -, L. Sarmili (Fakultas Teknik Geologi Universitas Padjadjaran, 2006)
This study focuses on the petrography characteristics of the volcanic rocks in Mount Komba, Flores Sea, Nusa Tenggara Timur.Based on textural and mineralogical characteristics, volcanic rocks Mount Komba are composed of andesite-basaltic lava flows. It is chiefly porphyritic, intergranular, intersertal to glomeroporphyritic clots textures that contains variable proportion of plagioclase, pyroxene, biotite, hornblende and opaque oxide minerals phenocryst in very fine grained groundmass contains clinopyroxene, plagopclase laths, devitrified glass and opaque oxide minerals. Plagioclase phenocrysts show sieve-textured cores, opaque inclusions, compositional zoning, and skeletal melt pockets. Pyroxenes are strong zones with rims. Some are poikilitic. Biotite commonly exhibits a deep russet color parallel to its slow ray, the perpendicular direction being light to medium yellow brown. Some are altered to an asseblage of chlorite and finely granular opaque oxide minerals. Hornblende is perhaps slightly less abundant than biotite and occurs typically in euhedral to subhedralo crystals. It is pleochroic in shade of olive green and brownish yellow, rarely exhibiting a bright apple-green shade. Among the accessory minerals, opaque oxide minerals occurs as euhedral wedge-shape or blocky to slightly rounded, broken grains are common and also as a fine grainded alteration product associated with chlorite, formed from biotite and hornblende. Fresh glass is present, though in most cases the glass is devitrified.Some Mount Komba volcanic rocks studied exhibit varying degrees of propylitic or sericitic alteration. Feldspars plagioclase in particular, in most of the intensely hydrothermally altered Mount Komba volcanic rocks have been replaced by fine grained sericite, clay minerals, carbonate, chlorite, epidote and opaque oxide minerals.